Original researchGenetic variability and the risk of myocardial infarction in Poles under 45 years of age - Sakowicz, Agata; Fendler, Wojciech; Lelonek, Małgorzata; Pietrucha, Tadeusz (Archives of Medical Science, 2010)
Introduction: Myocardial infarction is caused by the obstruction of an artery in places of atherosclerosis plaque rupture. Endothelial cells during their activation express chemoattractant and adhesion molecules whereas infiltrating inflammatory cells produce enzymes, predisposing a lesion to rupture. Material and methods: We investigated the correlation between polymorphisms in the human genes E-selectin (Ser128Arg), ICAM1 (K469E), OLR1 (K167N), MMP1 (1G/2G) and MMP3 (-1612 5A/6A) and the risk of MI in young Poles under 45 years. There was no significant difference in the frequency of single nucleotide polymorphism (SNP) of the studied genes E-selectin (Ser128Arg), ICAM1 (K469E), OLR1 (K167N) and MMP3 (–1612 5A/6A) between patients with MI and controls. Results: The analysis of the association of the 1G2G polymorphism with the risk of myocardial infarction indicated an odds ratio (OR) of 5.68 (95% confidence interval [95% CI] 2.60 to 12.36). Other factors associated with myocardial infarction were: smoking (OR 4.12; 95% CI 1.63-10.44), male sex (OR 16.02; 95% CI 5.90-43.46), hypercholesterolaemia (OR 2.74; 95% CI 1.29-5.83) and arterial hypertension (OR 4.56; 95% CI 1.66-14.47). Conclusions: We found that only MMP1 1G/2G polymorphism is associated with myocardial infarction in the Polish population of individuals younger than 45 years. Clinical factors seemed to play a greater role in the analysed group.